2018
DOI: 10.1186/s12968-018-0441-3
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of skeletal muscle microvascular perfusion of lower extremities by cardiovascular magnetic resonance arterial spin labeling, blood oxygenation level-dependent, and intravoxel incoherent motion techniques

Abstract: BackgroundNoninvasive cardiovascular magnetic resonance (CMR) techniques including arterial spin labeling (ASL), blood oxygenation level-dependent (BOLD), and intravoxel incoherent motion (IVIM), are capable of measuring tissue perfusion-related parameters. We sought to evaluate and compare these three CMR techniques in characterizing skeletal muscle perfusion in lower extremities and to investigate their abilities to diagnose and assess the severity of peripheral arterial disease (PAD).MethodsFifteen healthy … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
27
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 35 publications
(28 citation statements)
references
References 43 publications
1
27
0
Order By: Relevance
“…Blood oxygenation level‐dependent imaging detects deoxygenated hemoglobin and is most commonly used to detect regional changes in blood flow in the context of functional MRI of the brain. Although preliminary data for these techniques in muscle are promising, neither of these techniques has as yet been studied in the human muscular dystrophy population …”
Section: Evaluating Muscle Perfusion or Vascular Statusmentioning
confidence: 99%
See 1 more Smart Citation
“…Blood oxygenation level‐dependent imaging detects deoxygenated hemoglobin and is most commonly used to detect regional changes in blood flow in the context of functional MRI of the brain. Although preliminary data for these techniques in muscle are promising, neither of these techniques has as yet been studied in the human muscular dystrophy population …”
Section: Evaluating Muscle Perfusion or Vascular Statusmentioning
confidence: 99%
“…Although preliminary data for these techniques in muscle are promising, neither of these techniques has as yet been studied in the human muscular dystrophy population. 106,107…”
Section: Evaluating Muscle Fibrosismentioning
confidence: 99%
“…In PAD, using contact-free methods, such as HSI, LSCI, or MRI, may be preferable, especially when patients have foot ulcers. MR BOLD imaging is the most reliable technique to detect and stratify microvascular function at rest in PAD patients [23]. Disadvantages of BOLD MRI are the limited availability and the high costs [61].…”
Section: Discussionmentioning
confidence: 99%
“…Baseline T2* values of BOLD MRI (ms), ASL-blood flow (mL/ 100 g/min) and IVIM-f (%) were specified for different muscle groups between age-matched healthy controls and patients with PAD. According to Suo et al [23] T2* was the only perfusion-related parameter that showed significant differences between age-matched healthy controls and patients with PAD. Values derived from four muscle groups in the lower extremity are provided in Table 1.…”
Section: Application Within Padmentioning
confidence: 98%
See 1 more Smart Citation